The effect of stabilizing elements specifically titanium and niobium on the susceptibility of ferritic stainless steels to solidification cracking - Pistorius, P.G.H. (Pieter) (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2018.